Considering social differentiation in innovation and scaling - McGuire, Erin; Kabirigi, Michel; Ewell, Hanna; Liani, Millicent (2024)
How can we, and those who have been structurally excluded, become more robust AR4D actors? How can we educate ourselves to excel in interdisciplinary work and recognize biases within our project teams? What are the consequences of failing to address these systemic issues to our effectiveness?